Effect of antibiotic stewardship interventions in primary care on antimicrobial resistance of Escherichia coli bacteraemia in England (2013–18): a quasi-experimental, ecological, data linkage study. Issue 12 (December 2021) - Aliabadi, Shirin; Anyanwu, Philip; Beech, Elizabeth; Jauneikaite, Elita; Wilson, Peter; Hope, Russell; Majeed, Azeem; Muller-Pebody, Berit; Costelloe, Céire
Summary: Background: Antimicrobial resistance is a major global health concern, driven by overuse of antibiotics. We aimed to assess the effectiveness of a national antimicrobial stewardship intervention, the National Health Service (NHS) England Quality Premium implemented in 2015–16, on broad-spectrum antibiotic prescribing and Escherichia coli bacteraemia resistance to broad-spectrum antibiotics in England. Methods: In this quasi-experimental, ecological, data linkage study, we used longitudinal data on bacteraemia for patients registered with a general practitioner in the English National Health Service and patients with E coli bacteraemia notified to the national mandatory surveillance programme between Jan 1, 2013, and Dec 31, 2018. We linked these data to data on antimicrobial susceptibility testing of E coli from Public Health England's Second-Generation Surveillance System. We did an ecological analysis using interrupted time-series analyses and generalised estimating equations to estimate the change in broad-spectrum antibiotics prescribing over time and the change in the proportion of E coli bacteraemia cases for which the causative bacteria were resistant to each antibiotic individually or to at least one of five broad-spectrum antibiotics (co-amoxiclav, ciprofloxacin, levofloxacin, moxifloxacin, ofloxacin), after implementation of the NHS England Quality Premium intervention in April, 2015. Findings: Before implementation of the Quality Premium, the rate of antibiotic prescribing for all five broad-spectrum antibiotics was increasing at rate of 0·2% per month (incidence rate ratio [IRR] 1·002 [95% CI 1·000–1·004], p=0·046). After implementation of the Quality Premium, an immediate reduction in total broad-spectrum antibiotic prescribing rate was observed (IRR 0·867 [95% CI 0·837–0·898], p<0·0001). This effect was sustained until the end of the study period; a 57% reduction in rate of antibiotic prescribing was observed compared with the counterfactual situation (ie, had the Quality Premium not been implemented). In the same period, the rate of resistance to at least one broad-spectrum antibiotic increased at rate of 0·1% per month (IRR 1·001 [95% CI 0·999–1·003], p=0·346). On implementation of the Quality Premium, an immediate reduction in resistance rate to at least one broad-spectrum antibiotic was observed (IRR 0·947 [95% CI 0·918–0·977], p=0·0007). Although this effect was also sustained until the end of the study period, with a 12·03% reduction in resistance rate compared with the counterfactual situation, the overall trend remained on an upward trajectory. On examination of the long-term effect following implementation of the Quality Premium, there was an increase in the number of isolates resistant to at least one of the five broad-spectrum antibiotics tested (IRR 1·002 [1·000–1·003]; p=0·047). Interpretation: Although interventions targeting antibiotic use can result in changes in resistance over a short period, they might be insufficient alone to curtail antimicrobial resistance. Funding: National Institute for Health Research, Economic and Social Research Council, Rosetrees Trust, and The Stoneygate Trust.